2009
DOI: 10.1159/000186690
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Physiological Functions of G12/13-Mediated Signaling Pathways

Abstract: Accumulating data indicate that G12 subfamily (Gα12/13)-mediated signaling pathways play pivotal roles in a variety of physiological processes, while aberrant regulation of this pathway has been identified in various human diseases. It has been demonstrated that Gα12/13-mediated signals form networks with other signaling proteins at various levels, from cell surface receptors to transcription factors, to regulate cellular responses. Gα12/13 have slow rates of nucleotide exchange and GTP hydrolysis, and specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 145 publications
(207 reference statements)
3
83
0
Order By: Relevance
“…Ga 13 signaling is required for myocardial migration S1pr2 has been shown to couple with diverse G proteins, in particular Ga 12 and Ga 13 , to mediate a variety of cellular responses (Skoura and Hla, 2009;Suzuki et al, 2009). We previously identified one Ga 12 and two Ga 13 (Ga 13 a and Ga 13 b) isoforms in zebrafish, and demonstrated that they are essential during gastrulation (Lin et al, 2005;Lin et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ga 13 signaling is required for myocardial migration S1pr2 has been shown to couple with diverse G proteins, in particular Ga 12 and Ga 13 , to mediate a variety of cellular responses (Skoura and Hla, 2009;Suzuki et al, 2009). We previously identified one Ga 12 and two Ga 13 (Ga 13 a and Ga 13 b) isoforms in zebrafish, and demonstrated that they are essential during gastrulation (Lin et al, 2005;Lin et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…S1pr2/Ga 13 signaling regulates myocardial migration via a RhoGEF/Rho-dependent pathway Next, we investigated the molecular effectors of S1pr2/Ga 13 -regulated myocardial migration. Ga 12 and Ga 13 function primarily by activating RhoGEF and then RhoA (Suzuki et al, 2009). We have previously shown that Ga 13 a binds a PDZRhoGEF known as Arhgef11, via its regulator of G protein-coupled signaling (RGS) domain, and that Ga 12/13 regulate zebrafish epiboly through a RhoGEF-dependent pathway.…”
Section: Research Articlementioning
confidence: 99%
“…Tyrosine phosphorylation is a commonly used mechanism for the regulation of RhoGEF activity and increased tyrosine phosphorylation following receptor activation has been reported for the three RGS-RhoGEFs family members (Chikumi et al, 2002;Guilluy et al, 2010;Suzuki et al, 2009;Suzuki et al, 2003). We treated MCF7-CXCR4 cells with CXCL12 and used a phosphotyrosine (PY)-specific antibody to immunoprecipitate PY-proteins (Fig.…”
Section: Stimulation Of Cxcr4 Leads To Tyrosine Phosphorylation Of Lsmentioning
confidence: 99%
“…To determine whether LSC or PRG was required for cell migration following stimulation of CXCR4, we used siRNA to selectively target LSC, LARG or PRG expression and assessed the effect on cell migration (Suzuki et al, 2009;Tesmer, 2009). Each siRNA reduced expression of its target gene by 90% or greater, without altering the expression of other RGS-RhoGEF proteins (Fig.…”
Section: Knockdown Of Prg Expression Profoundly Inhibits Cxcr4-mediatmentioning
confidence: 99%
“…GTP binding and activation of four classes of G proteins lead to stimulation of complex intracellular signaling networks. These include stimulation of adenylyl cyclase and production of cyclic AMP (cAMP) by Gα s , repression of cAMP production but stimulation of Src tyrosine kinase by members of activated G i proteins, activation of phospholipase Cβ (PLCβ) and subsequent release of intracellular Ca 2+ by G q family, and RhoGEF activation by G 12/13 [2][3][4]. Numerous studies have focused on the function of G protein signaling in differentiated, post-mitotic cells.…”
Section: Gpcr Signalingmentioning
confidence: 99%